Cooperative membership effects on farmers’ choice of milk marketing channels in Rwanda - Habiyaremye, Naphtal; Mtimet, Nadhem; Ouma, Emily A.; Obare, G.A. (Elsevier, 2023)
Although cooperatives play a critical role in reducing transaction costs and enhancing farmers’ adoption of better farming practices, little is known on the effects of dairy cooperative membership on the choice of milk marketing channels. This paper employs an endogenous switching probit model to estimate the determinants of farmers’ choice of milk marketing channels while controlling for the potential selection bias of cooperative membership. We find that cooperative membership has positive and significant effects on the choice of both MCCs and milk traders as marketing channels along with a negative effect on the choice of other buyers (direct consumers and restaurants). The varying effect of cooperative membership on choice of different marketing channels holds also for non-members had they been cooperative members. Furthermore, we find that the selling price positively affects farmers’ choice of MCCs, but the longer distance to MCCs may make farmers (including cooperative members) to choose milk traders who offer lower prices than MCCs. Since the MCCs are managed by dairy cooperatives and they are the only marketing channels that conduct basic milk quality tests while offering higher prices to farmers, we recommend policies that support easy access to MCCs and enhance dairy cooperatives’ governance. This will facilitate dairy farmers’ access to a better marketing channel while meeting an already growing consumer demand for products safety and quality in the food industry.